(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Anaesthetic management of patients undergoing third open-heart surgery presents significant challenges due to anatomical distortions, adhesions, and altered haemodynamics. Patients with complex comorbidities require meticulous planning to mitigate perioperative risks. Case description and management: This report presents the case of a 48-year-old man with severe mitral valve dysfunction and multiple comorbidities who underwent redo mitral valve replacement. A comprehensive anaesthetic management plan was tailored to the patient, incorporating invasive haemodynamic monitoring with a coordinated multidisciplinary strategy. Cardiopulmonary bypass was established using femorofemoral cannulation, ensuring haemodynamic stability during the procedure. Postoperative care involved vigilant monitoring of haemodynamic and respiratory complications. The patient experienced transient desaturation, which was effectively managed with targeted therapy. The patient was extubated on postoperative day three and discharged in stable condition. Conclusion: This case highlights the critical importance of multidisciplinary planning, individualised anaesthetic strategies, and proactive postoperative management in high-risk reoperative cardiac surgery to achieve favourable outcome.